Pengaruh senam aerobik low impact dan yoga terhadap aerobic endurance dan tingkat stres wanita usia 30-40 tahun - Kumaat, Noortje Anita; Caturia Sasti Sulistyana; Yudi Dwi Saputra (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Increases the age of a person then the effect on the physical conditions. Someone needs to do a sport that is measurable and regularly, especially in women age 30-40 years. This research aims to analyze the magnitude of the influence of low impact aerobic gymnastics and yoga to aerobic endurance and health stress, with the kind of quasy experimental research. Research instrument used a treadmill test to measure the aerobic endurance and perceived stress scale instrument for measure the health stress. The sample person 50 women age 30-40 years for low impact aerobic gymnastics and yoga group. The research for aerobic endurance on low impact aerobic gymnastic obtained increased an average of 1,85 ml/kg/min and the average yoga 1,7 ml/kg/min. to health stress on low impact aerobic gymnastics occur an decrease amount to 5,5 points and yoga of 7,65 points. Next to the t-test results obtained, there was a significant difference in increase influence on health stress (P<0,05) and aerobck endurance there was no significant difference in its increase (P>0,05). So that the low impact aerobic gymnastics further enhance aerobic endurance and yoga further decrease of stress level that enhance health stress.